The Correlation of Self Management Behavior with Quality of Life in Patients with Primary Hypertension - Ni Kadek Yuni Lestari; Ni Luh Gede Intan Saraswati (GLOBAL HEALTH SCIENCE GROUP, 2022)
Hypertension is a cardiovascular disease that is a major concern because of the high morbidity and mortality rates. Uncontrolled hypertension will cause various complications will interfere quality of life the patient with hypertension. Quality of life in hypertensive patients is influenced by the severity and severity of complications experienced by the patient. Self management behavior as a disease management to support patients with chronic diseases, behavior modification is very useful to reduce or delay the adverse effects of hypertension. The purpose of this study was to determine the correlation between self-management behavior and quality of life in patients with primary hypertension at UPTD Puskesmas Manggis I Karangasem. This research is a descriptive quantitative correlational research with a cross sectional approach. The sample of this study was 79 respondents who were selected through simple random sampling technique, data analysis used Spearman Rank test. The results showed that 31 respondents (39.2%) had good self-management behavior and 34 respondents (43.1%) had good quality of life. The results of the Rank Spearman test, p value = 0.000 (≤0.05) showed a significant correlation between self-management behavior and quality of life in patients with primary hypertensive. The correlation coefficient value (r) 0.835 means a very strong correlation between self-management behavior and quality of life. Nurses are expected to be able to provide education about self-management behavior that they can improve the quality of life patients with hypertension.